Method for preparing high-purity ammonium metavanadate by efficiently removing silicon
Through flocculation and electrophoresis, the multi-step method of strengthening the decomposition and ammonium metavanadate crystallization is solved, and the purity of ammonium metavanadate is limited by silicon impurities in the traditional method is achieved, which effectively removes silicon impurities, improves vanadium recovery and purity, and is suitable for industrial production.
Patent Information
- Application Number
- CN202510037943.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-11
AI Technical Summary
The purity of ammonium metavanadate in traditional methods is limited by silicon impurities. The existing silicon removal method is not efficient and may introduce new impurities or generate a large amount of wastewater, making it difficult to meet the high purity requirements.
The multi-step method of combining flocculation and decomposition-electrophoresis-strengthening decomposition-ammonium metavanadate crystal is adopted. By polymerizing aluminum chloride or polymeric aluminum sulfate as silicone removal agent, combined with electrophoresis and flocculant stand-alt settlement, the pH value and voltage are controlled, and finally cooling and crystallization is carried out to obtain high-purity ammonium metavanadate.
It effectively reduces the silicon content in ammonium metavanadate to below 200ppm, improves vanadium recovery and purity, reduces energy consumption and wastewater generation, and is suitable for industrial production.
Smart Images

Figure CN119797424A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ammonium metavanadate preparation, in particular to a method for preparing high-purity ammonium metavanadate by efficient silicon removal. Background Art
[0002] High-purity ammonium metavanadate (NH4VO3) is an important chemical raw material, widely used in the production of high-purity vanadium oxides, catalysts, vanadium electrolytes, etc. With the advancement of science and technology and the improvement of environmental protection requirements, the demand for high-purity ammonium metavanadate has steadily increased, especially in vanadium energy storage projects. The development of all-vanadium flow batteries has brought new market opportunities for high-purity ammonium metavanadate.
[0003] In the comprehensive utilization of vanadium resources, ammonium metavanadate, as an important vanadium compound, is widely used in the fields of catalysts, vanadium battery electrolytes, etc. However, the purity of ammonium metavanadate in traditional methods is often limited by the silicon impurities therein, and a new purification technology is needed to meet the high purity requirements. The silicon removal methods in the prior art are usually inefficient and may introduce new impurities or produce a large amount of wastewater, which is not conducive to environmental protection and cost control. The present invention provides a new method, which can efficiently remove silicon impurities in ammonium vanadate solution without generating additional wastewater through a specific chemical treatment step, and prepare high-purity ammonium metavanadate.
[0004] Chinese patent document CN114480883A discloses a method for preparing high-purity vanadium pentoxide by synergistically removing silicon and chromium from a vanadium solution by using nickel ions. The method first adjusts the acidity of the vanadium-containing solution for reduction, then adjusts and adds nickel to remove silicon and chromium, and then adds ammonium salt to prepare ammonium metavanadate after filtering. Although this method can obtain ammonium metavanadate, it is necessary to adjust the acidity of the solution first and then adjust the alkali to remove the silicon from the vanadium-containing solution, which has high acid and alkali consumption, high process cost, and produces a lot of process wastewater, which does not meet actual production conditions.
[0005] Chinese patent document CN104843789A discloses a method for purifying vanadium pentoxide, wherein the method first acidifies calcium vanadate after calcification of a vanadium-containing solution, adds an impurity remover for purification, adjusts the pH, adds ammonium sulfate to precipitate ammonium polyvanadate, and finally prepares vanadium pentoxide by evaporating water and ammonia in the solution. Although this method can produce vanadium pentoxide, the process is complicated, the vanadium extraction process requires a lot of energy consumption, and the processing cost is high, which does not meet the actual production conditions.
[0006] In recent years, the recycling and purification technology of vanadium resources and environmentally friendly purification processes have received more and more attention. The method of preparing high-purity ammonium metavanadate from ammonium vanadate needs further research to achieve the goal of simplifying, diversifying and cleaning the vanadium recycling and purification process. Summary of the invention
[0007] The invention provides a method for preparing high-purity ammonium metavanadate by efficient silicon removal. The method has simple leaching conditions and is easy to operate, has a high vanadium recovery rate, good purification effect, low energy consumption, high vanadium resource utilization rate, and broad application prospects in the industrial recovery of vanadium resources.
[0008] In view of this, the scheme of the present invention is:
[0009] A method for preparing high-purity ammonium metavanadate by efficient silicon removal, comprising the following steps:
[0010] S1. After the ammonium polyvanadate is dissolved, ammonia water is added to carry out an ammonium conversion reaction to obtain an ammonium conversion solution;
[0011] S2. Control the pH value of the ammonium solution to 8-8.5, and add a desiliconizing agent to perform a desiliconizing reaction; the desiliconizing agent is polyaluminum chloride and / or polyaluminum sulfate;
[0012] S3. The solution after the silicon removal reaction is placed in an electric sedimentation tank for electrophoretic sedimentation, and a flocculant is added to allow the solution to settle, and the purified solution is filtered; the flocculant is a cationic polyacrylamide;
[0013] S4. Cooling and crystallizing the purified liquid, and filtering to obtain high-purity ammonium metavanadate.
[0014] Further, in step S1:
[0015] The impurities in the ammonium polyvanadate include: Si 0.3-0.8%, Ca 0.1-0.3%, Al 0.1-0.3%, and the sum of Na2O and K2O 1.2-2.4%; the content of Si can be 0.30%, 0.35%, 0.40%, 0.45%, 0.50%, 0.55%, 0.60%, 0.65%, 0.70%, 0.75% or 0.80%, etc.; the content of Na2O+K2O can be 1.2%, 1.3%, 1.5%, 1.9%, 2.0%, 2.1%, 2 .2% or 2.4%, etc.; the Ca content can be 0.1%, 0.14%, 0.15%, 0.18%, 0.25%, 0.28%, 0.29% or 0.3%, etc.; the Al content can be 0.1%, 0.14%, 0.16%, 0.18%, 0.23%, 0.25%, 0.29% or 0.3%, etc., but is not limited to the listed values, and other values not listed within the range are equally applicable.
[0016] The source of the ammonium polyvanadate can be a primary product prepared by roasting, leaching, vanadium precipitation, etc., from raw materials such as vanadium slag and stone coal. The content of V2O5 in the ammonium polyvanadate is 85-90%, more preferably 87-89%, for example, 87.0%, 87.3%, 88.0%, 88.5%, 88.3%, 88.6% or 89.0%, etc.
[0017] It should be noted that the content of V2O5 in the ammonium polyvanadate used in the method for preparing high-purity ammonium metavanadate of the present invention is essentially not limited, and the same is applicable to V2O5 with a higher content when similar impurities are present; for V2O5 with a lower content, it is only necessary to adaptively adjust the amount of reagents when a higher content of impurities is present.
[0018] Further, in step S1, during the transammonium reaction process, ammonia water is added to a pH value of 7-9, which may be 7.0, 7.5, 8.0, 8.5, 9.0, etc.; the transammonium reaction time is 0.5-1h, which may be 0.50h, 0.55h, 0.60h, 0.65h, 0.70h, 0.75h, 0.80h, 0.85h, 0.90h, 0.95h or 1.00h, etc., but is not limited to the listed values, and other values not listed within the range are also applicable.
[0019] The pH of the ammonium polyvanadate conversion reaction is controlled within the above range to avoid the situation where the ammonium polyvanadate is wrapped up due to too low or too high pH, thereby affecting the conversion rate, and effectively ensure the effective removal of impurity elements in the ammonium metavanadate.
[0020] Further, in step S2, the pH of the ammonium transfer solution can be controlled to be 8.0, 8.11, 8.22, 8.28, 8.3, 8.35, 8.4, 8.43, 8.48, 8.49 or 8.5, etc.; the concentration of the silicon removal agent is 10-15wt%, which can be 10.0%, 10.5%, 11.0%, 11.5%, 12.0%, 12.5%, 13.0%, 13.5%, 14.0%, 14.5% or 15.0%, etc.; the amount of the silicon removal agent used per liter of ammonium transfer solution is 2-5mL, which can be 2.0mL, 2.5mL, 3.0mL, 3.5mL, 4.0mL, 4.5mL or 5.0mL, and the amount added can be determined according to the content of silicon impurities.
[0021] Further, in step S2, the reaction temperature of the silicon removal process is 75-85°C, for example, it can be 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C or 85°C; the silicon removal reaction leaching time is 1-2h, which can be 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2.0h, etc.
[0022] The principle of silicon removal by polyaluminium sulfate or polyaluminium chloride is to use aluminium salt to hydrolyse under weak alkaline conditions to generate aluminium hydroxide. Aluminium hydroxide solid has a large specific surface area, strong adsorption performance, and carries a positive charge, which can adsorb negatively charged silica gel in the solution, thereby achieving the purpose of silicon removal. Aluminium hydroxide needs to remove silica gel colloid in the pH range of 8-8.5. Al is an amphoteric metal, which will dissolve under acidic or strongly alkaline conditions, and cannot form a solid with strong adsorption characteristics to achieve the purpose of impurity removal, so it needs to be within the appropriate pH range.
[0023] Further, in step S2, the silicon removal reaction leaching stirring rate is 300-500r / min, for example, it can be 300r / min, 320r / min, 340r / min, 460r / min, 380r / min, 400r / min, 420r / min, 440r / min, 460r / min, 480r / min or 500r / min, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0024] Further, in step S3:
[0025] The voltage of the electrophoretic sedimentation process is 0.3-0.8V, for example, it can be 0.3V, 0.44V, 0.59V, 0.63V, 0.7V, 0.75V, 0.78V or 0.8V, etc.; the sedimentation time is 0.5-1h, for example, it can be 0.5h, 0.55h, 0.58h, 0.6h, 0.66h, 0.7h, 0.76h, 0.88h, 0.96h or 1h;
[0026] The anode of the electrophoresis sedimentation tank is a stainless steel electrode, a nickel electrode, or a ruthenium-plated titanium electrode, and the cathode is a graphite electrode or a glassy carbon electrode.
[0027] Aluminum-containing polymer desiliconizer uses positively charged aluminum hydroxide solid to adsorb negatively charged silicate ions, and removes silicon after neutralization. However, due to the limitation of chemical reaction balance, a very small amount of silicate ions cannot be completely removed. The use of an electrophoretic sedimentation tank can "aggregate" the silicate ions that have not undergone neutralization reaction at the anode of the electrolytic cell, thereby increasing the local concentration of silicate ions. In this way, by adding subsequent cationic polyacrylamide to the anode of the electrophoretic sedimentation tank and utilizing the long chain effect of organic macromolecular polyacrylamide, the silicate ions can be further "aggregated", thereby improving the interfacial mass transfer reaction effect with the positively charged aluminum hydroxide particles, thereby achieving the purpose of deep desiliconization. In this process, a small amount of Na + and K +It also combines with Al and Si to form fine sodium aluminosilicate colloidal particles, achieving the purpose of simultaneous removal of Na and K. The method of combining electrophoresis with flocculants can greatly accelerate the occurrence of silicon precipitation reaction, reduce flocculation sedimentation time, and obtain a clear silicon removal solution.
[0028] Further, in step S3:
[0029] The molecular weight of the flocculant is 10 million to 30 million, for example, 10 million, 12 million, 14 million, 16 million, 18 million, 20 million, 22 million, 24 million, 26 million, 28 million or 30 million;
[0030] The concentration of the flocculant is 1-3g / L, which can be 1.0g / L, 1.2g / L, 1.4g / L, 1.6g / L, 1.8g / L, 2.0g / L, 2.2g / L, 2.4g / L, 2.6g / L, 2.8g / L or 3.0g / L; the amount of flocculant added per liter of silicon removal reaction solution is 5-10mL, and the static sedimentation time is 2-5min; the amount of flocculant added can be 5.0mL / L, 5.5mL / L, 6.0mL / L, 6.5mL / L L, 7.0mL / L, 7.5mL / L, 8.0mL / L, 8.5mL / L, 9.0mL / L, 9.5mL / L or 10.0mL / L; the static sedimentation time can be 2min, 2.1min, 2.4min, 2.6min, 3.1min, 3.6min, 3.8min, 4.1min, 4.5min or 5.0h, and the standing time is determined according to the silicon impurity content and the amount of flocculant added to ensure the effect of flocculation sedimentation in removing silicon impurities.
[0031] Further, in step S4:
[0032] The pH value of the crystallization process is 8.5-9.0, which can be 8.50, 8.55, 8.60, 8.65, 8.70, 8.75, 8.80, 8.85, 8.90, 8.95 or 9.00; after silicon removal and purification, the purity of the vanadium product can be further purified by the ammonium metavanadate crystallization method, especially the cationic impurities and silicon in the initial ammonium polyvanadate, to provide a guarantee for obtaining a vanadium product of higher purity. The crystallization of ammonium metavanadate needs to be maintained within the appropriate range of pH = 8.5-9.0. Too high or too low pH will reduce the crystallization rate of ammonium metavanadate;
[0033] The crystallization temperature is 30-50°C, and the crystallization time is 2-4h; the crystallization temperature can be 30°C, 32°C, 34°C, 36°C, 38°C, 40°C, 42°C, 44°C, 46°C, 48°C or 50°C, and the cooling crystallization time can be 2.0h, 2.2h, 2.4h, 2.6h, 2.8h, 3.0h, 3.2h, 3.4h, 3.6h, 3.8h or 4.0h.
[0034] Furthermore, in step S4, the mother liquor obtained after the crystallization filtration is used to dissolve ammonium polyvanadate in step S1.
[0035] Further, in step S1, the ammonium polyvanadate can be dissolved using water or the mother liquor obtained by crystallization filtration in step S4, and the liquid-to-solid ratio is (15-20):1, for example, it can be 15.0:1, 15.5:1, 16.0:1, 16.5:1, 17.0:1, 17.5:1, 18.0:1, 18.5:1, 19.0:1, 19.5:1 or 20.0:1, etc.; the temperature of the dissolution process is 90-100°C, for example, it can be 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C or 100°C, etc., but is not limited to the listed values, and other values not listed within the range are also applicable.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] The preparation method of the present invention utilizes a multi-step method combining flocculation impurity removal-electrophoresis enhanced impurity removal-ammonium metavanadate crystallization, which are combined and promoted with each other, and can effectively reduce the silicon content in the ammonium metavanadate to below 200 ppm, thereby achieving the purpose of efficient desiliconization; the preparation process has a short reaction flow, low energy consumption loss, no additional wastewater generation, simple operation, low cost, clean and environmentally friendly, more beneficial to environmental protection, and can realize industrial production.
[0038] The high-purity ammonium metavanadate prepared by the preparation method of the present invention has high purity, low impurity element content and high vanadium recovery rate, and can meet the purity requirements of vanadium products used in electrolyte and aviation manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The present invention is a flow chart of a method for preparing high-purity ammonium metavanadate by efficient silicon removal provided in a specific embodiment of the present invention. DETAILED DESCRIPTION
[0040] The technical solution of the present invention will be clearly and completely described below in conjunction with the preferred embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] In one embodiment, a method for preparing high-purity ammonium metavanadate by efficient silicon removal is provided, and the specific process is as follows: Figure 1 As shown, the steps include:
[0042] S1. After the ammonium polyvanadate is dissolved, aqueous ammonia is added to carry out an ammonium conversion reaction to obtain an ammonium conversion solution;
[0043] S2. Maintaining the pH value of the ammonium solution at 8-8.5, adding a silicon removal agent to the ammonium solution for silicon removal reaction; the silicon removal agent is polyaluminium chloride and / or polyaluminium sulfate;
[0044] S3. The solution after the silicon removal reaction is placed in an electric sedimentation tank for electrophoretic sedimentation, and a flocculant is added to allow the solution to settle, and the purified solution is filtered; the flocculant is a cationic polyacrylamide;
[0045] S4. Cooling and crystallizing the purified liquid, and filtering to obtain high-purity ammonium metavanadate.
[0046] In the above embodiment, by utilizing a multi-step method combining flocculation impurity removal-electrophoresis enhanced impurity removal-ammonium metavanadate crystallization, the steps are combined and promoted to effectively reduce the silicon content in the ammonium metavanadate to below 200 ppm, thereby achieving the purpose of efficient desiliconization. The high-purity ammonium metavanadate obtained by the preparation method has high purity, low content of impurity elements, and high vanadium recovery rate, which can meet the purity requirements of vanadium products used in electrolytes and aviation manufacturing.
[0047] The following are preferred implementation examples. For those reagents or instrument manufacturers not specified in the examples, conventional products can be purchased on the market. For those without specific conditions, conventional conditions or manufacturer recommended conditions can be followed. Unless otherwise specified, the data indicating the proportion of components such as "content" and "concentration" are all mass proportions. In the example, the ammonium polyvanadate is a primary product prepared by roasting, leaching, and vanadium precipitation of raw materials such as vanadium slag and stone coal. The content of V2O5 in the ammonium polyvanadate is 85-90%, and impurities include: Si 0.3-0.8%, Ca 0.1-0.3%, Al 0.1-0.3%, and the sum of Na2O and K2O 1.2-2.4%.
[0048] Example 1
[0049] Ammonium polyvanadate with a V2O5 content of 85% was selected as the purification raw material, wherein the impurity content was: Si 0.8%, Ca 0.3%, Al 0.3%, and the sum of Na2O and K2O 2.4%.
[0050] 1) Ammonium polyvanadate and hot water are mixed at a ratio of 15:1, heated and ammonia water is added to adjust the solution pH to 8, and the ammonium conversion reaction time is 0.5h. At this time, the ammonium polyvanadate is completely dissolved to form an ammonium metavanadate solution. The impurity content in the solution is: Si 0.176g / L, Ca 0.059g / L, Al 0.059g / L, Na2O+K2O0.706g / L.
[0051] 2) Add 2 mL / L of 10% polyaluminium chloride to the ammonium conversion solution for silicon removal. The silicon removal reaction is carried out at 75°C for 1 hour. The impurity content of the silicon-free liquid obtained after filtration is: Si 0.066 g / L, Ca 0.059 g / L, Al 0.079 g / L, Na2O+K2O 0.706 g / L.
[0052] 3) The solution with silicon removal agent added was transferred to an electrophoretic sedimentation tank (anode was a stainless steel electrode, cathode was a graphite electrode), and electrophoretic sedimentation was performed for 0.5 h at a voltage of 0.3 V. After electrophoretic sedimentation, 1 g / L cationic polyacrylamide with a molecular weight of 10 million and 5 mL / L was added to the electrophoretic sedimentation tank for flocculation sedimentation, and filtered after standing for 2 min. After filtration, a clarified impurity-removed liquid was obtained, and the impurity components of the impurity-removed liquid were: Si 0.021 g / L, Ca 0.059 g / L, Al 0.049 g / L, Na2O+K2O 0.206 g / L.
[0053] 4) adjusting the pH of the solution to 8.5, and then cooling and crystallizing, the crystallization temperature is 50°C, the crystallization time is 2 hours, and the slurry is filtered after crystallization to obtain high-purity ammonium metavanadate and crystallization mother liquor, and the crystallization mother liquor is returned to step (1) for ammonium conversion reaction. The impurity components of the crystallization mother liquor are: Si 0.018g / L, Ca 0.039g / L, Al 0.022g / L, Na2O+K2O 0.186g / L.
[0054] The high-purity ammonium metavanadate finally produced has a purity of 99.7%, and the impurity contents are respectively 0.011% Si, 0.039% Ca, 0.031% Al, and 0.23% Na2O+K2O.
[0055] Example 2
[0056] Ammonium polyvanadate with a V2O5 content of 90% was selected as a purification raw material, wherein the impurity content was: Si 0.3%, Ca 0.1%, Al 0.1%, and the sum of Na2O and K2O 1.2%.
[0057] 1) Ammonium polyvanadate and hot water are mixed at a ratio of 15:1, heated and ammonia water is added to adjust the solution pH to 8.5, and the ammonium conversion reaction time is 1 hour. At this time, the ammonium polyvanadate is completely dissolved to form an ammonium metavanadate solution, and the impurity content in the solution is: Si 0.2g / L, Ca 0.067g / L, Al 0.067g / L, Na2O+K2O 0.8g / L.
[0058] 2) Add 5 mL / L of 15% polyaluminium chloride to the ammonium conversion solution for silicon removal. The silicon removal reaction is carried out at 85°C for 2 hours. The impurity contents of the silicon-free liquid obtained after filtration are as follows: Si 0.046 g / L, Ca 0.059 g / L, Al 0.055 g / L, and Na2O+K2O 0.706 g / L.
[0059] 3) The solution with silicon removal agent added was transferred to an electrophoretic sedimentation tank (anode was a nickel electrode, cathode was a glassy carbon electrode), and electrophoretic sedimentation was performed at a voltage of 0.8 V for 1 hour. After electrophoretic sedimentation, 10 mL / L of cationic polyacrylamide with a molecular weight of 30 million was added to the electrophoretic sedimentation tank for flocculation sedimentation, and filtered after standing for 5 minutes. After filtration, a clarified impurity-removed liquid was obtained, and the impurity components of the impurity-removed liquid were: Si 0.021 g / L, Ca 0.049 g / L, Al 0.049 g / L, Na2O+K2O 0.21 g / L.
[0060] 4) adjusting the pH of the solution to 9, and then cooling and crystallizing, the crystallization temperature is 30°C, the crystallization time is 4 hours, and the slurry is filtered after crystallization to obtain high-purity ammonium metavanadate and crystallization mother liquor, and the crystallization mother liquor is returned to step (1) for ammonium conversion reaction. The impurity components of the crystallization mother liquor are: Si 0.018g / L, Ca 0.039g / L, Al 0.022g / L, Na2O+K2O 0.18g / L.
[0061] The high-purity ammonium metavanadate finally produced has a purity of 99.8%, and the impurity contents are 0.018% Si, 0.042% Ca, 0.030% Al, and 0.18% Na2O+K2O.
[0062] Example 3
[0063] Ammonium polyvanadate with a V2O5 content of 89% was selected as a purification raw material, wherein the impurity content was: Si 0.5%, Ca 0.2%, Al 0.2%, and the sum of Na2O and K2O 2.0%.
[0064] 1) Ammonium polyvanadate and hot water are mixed at a ratio of 15:1, heated and ammonia water is added to adjust the solution pH to 8.3, and the ammonium conversion reaction time is 0.8h. At this time, the ammonium polyvanadate is completely dissolved to form an ammonium metavanadate solution. The impurity content in the solution is: Si 0.333g / L, Ca 0.133g / L, Al 0.133g / L, Na2O+K2O1.32g / L.
[0065] 2) 3 mL / L of 13% polyaluminium chloride was added to the ammonium conversion solution for silicon removal. The silicon removal reaction was carried out at 80°C for 1.4 h. The impurity content of the desiliconized liquid obtained after filtration was: Si 0.06 g / L, Ca 0.039 g / L, Al 0.079 g / L, Na2O+K2O 1.16 g / L.
[0066] 3) The solution with silicon removal agent added was transferred to the electrophoretic sedimentation tank (the anode was a stainless steel electrode and the cathode was a graphite electrode) and electrophoretically sedimented for 0.6 h at a voltage of 0.55 V. After electrophoretic sedimentation, 7 mL / L of cationic polyacrylamide with a molecular weight of 3 g / L and a molecular weight of 12 million was added to the electrophoretic sedimentation tank for flocculation sedimentation. After standing for 4 minutes, the solution was filtered to obtain a clarified impurity-removed liquid. The impurity components of the impurity-removed liquid were: Si 0.028 g / L, Ca 0.039 g / L, Al 0.055 g / L, and Na2O+K2O 0.56 g / L.
[0067] 4) adjusting the pH of the solution to 8.6, and then cooling and crystallizing, the crystallization temperature is 35°C, the crystallization time is 3h, and the slurry is filtered after crystallization to obtain high-purity ammonium metavanadate and crystallization mother liquor, and the crystallization mother liquor is returned to step (1) for ammonium conversion reaction. The impurity components of the crystallization mother liquor are: Si 0.012g / L, Ca 0.039g / L, Al 0.033g / L, Na2O+K2O 0.28g / L.
[0068] The high-purity ammonium metavanadate finally produced has a purity of 99.56%, and the impurity contents are respectively 0.012% Si, 0.041% Ca, 0.032% Al, and 0.21% Na2O+K2O.
[0069] Example 4
[0070] Ammonium polyvanadate with a V2O5 content of 86% was selected as a purification raw material, wherein the impurity content was: Si 0.6%, Ca 0.22%, Al 0.19%, and the sum of Na2O and K2O 1.8%.
[0071] 1) Ammonium polyvanadate and hot water are mixed at a ratio of 15:1, heated and ammonia water is added to adjust the solution pH to 8.3, and the ammonium conversion reaction time is 0.5h. At this time, the ammonium polyvanadate is completely dissolved to form an ammonium metavanadate solution. The impurity content in the solution is: Si 0.4g / L, Ca 0.147g / L, Al 0.127g / L, Na2O+K2O1.2g / L.
[0072] 2) 4 mL / L of 11% polyaluminium chloride was added to the ammonium conversion solution for silicon removal. The silicon removal reaction was carried out at 78°C for 1 hour. The impurity content of the desiliconized liquid obtained after filtration was: Si 0.04 g / L, Ca 0.09 g / L, Al 0.11 g / L, Na2O+K2O 0.93 g / L.
[0073] 3) The solution with silicon removal agent added was transferred to the electrophoresis sedimentation tank (the anode was a ruthenium-plated titanium electrode, and the cathode was a glassy carbon electrode), and electrophoresis sedimentation was performed at a voltage of 0.59 V for 0.5 h. After electrophoresis sedimentation, 2 g / L cationic polyacrylamide with a molecular weight of 20 million and 5 mL / L was added to the electrophoresis sedimentation tank for flocculation sedimentation, and filtered after standing for 2 minutes. After filtration, a clarified impurity-removed liquid was obtained, and the impurity components of the impurity-removed liquid were: Si 0.021 g / L, Ca 0.069 g / L, Al 0.049 g / L, Na2O+K2O 0.6 g / L.
[0074] 4) adjusting the pH of the solution to 8.5, and then cooling and crystallizing, the crystallization temperature is 45°C, the crystallization time is 2 hours, and the slurry is filtered after crystallization to obtain high-purity ammonium metavanadate and crystallization mother liquor, and the crystallization mother liquor is returned to step (1) for ammonium conversion reaction. The impurity components of the crystallization mother liquor are: Si 0.021g / L, Ca 0.069g / L, Al 0.042g / L, Na2O+K2O 0.44g / L.
[0075] The high-purity ammonium metavanadate finally produced has a purity of 99.66%, and the impurity contents are respectively 0.011% Si, 0.033% Ca, 0.030% Al, and 0.21% Na2O+K2O.
[0076] Example 5
[0077] Ammonium polyvanadate with a V2O5 content of 88% was selected as a purification raw material, wherein the impurity content was: Si 0.5%, Ca 0.12%, Al 0.13%, and the sum of Na2O and K2O 1.55%.
[0078] 1) Ammonium polyvanadate and hot water are mixed at a ratio of 17:1, heated and ammonia water is added to adjust the solution pH to 8.5, and the ammonium conversion reaction time is 0.5h. At this time, all the ammonium polyvanadate is dissolved to form an ammonium metavanadate solution. The impurity content in the solution is: Si 0.294g / L, Ca 0.071g / L, Al 0.077g / L, Na2O+K2O 0.911g / L.
[0079] 2) Add 2 mL / L of 14% polyaluminium chloride to the ammonium conversion solution for silicon removal. The silicon removal reaction is carried out at 75°C for 2 hours. The impurity content of the silicon-free liquid obtained after filtration is: Si 0.032 g / L, Ca 0.070 g / L, Al 0.068 g / L, Na2O+K2O 0.671 g / L.
[0080] 3) The solution with silicon removal agent added was transferred to the electrophoretic sedimentation tank (the anode was a stainless steel electrode and the cathode was a graphite electrode) and electrophoretically sedimented for 0.5 h at a voltage of 0.76 V. After electrophoretic sedimentation, 1 g / L cationic polyacrylamide with a molecular weight of 24 million and 5 mL / L was added to the electrophoretic sedimentation tank for flocculation sedimentation. After standing for 2 min, the solution was filtered to obtain a clarified impurity-removed liquid. The impurity components of the impurity-removed liquid were: Si 0.029 g / L, Ca 0.061 g / L, Al 0.043 g / L, and Na2O+K2O 0.446 g / L.
[0081] 4) adjusting the pH of the solution to 8.5, and then cooling and crystallizing, the crystallization temperature is 30°C, the crystallization time is 2 hours, and the slurry is filtered after crystallization to obtain high-purity ammonium metavanadate and crystallization mother liquor, and the crystallization mother liquor is returned to step (1) for ammonium conversion reaction. The impurity components of the crystallization mother liquor are: Si 0.028g / L, Ca 0.034g / L, Al 0.040g / L, Na2O+K2O 0.494g / L.
[0082] The high-purity ammonium metavanadate finally produced has a purity of 99.75%, and the impurity contents are respectively 0.015% Si, 0.034% Ca, 0.032% Al, and 0.19% Na2O+K2O.
[0083] Example 6
[0084] Ammonium polyvanadate with a V2O5 content of 88.6% was selected as a purification raw material, wherein the impurity content was: Si 0.32%, Ca 0.15%, Al 0.13%, and the sum of Na2O and K2O 1.14%.
[0085] 1) Ammonium polyvanadate and hot water are mixed at a ratio of 15:1, heated and ammonia water is added to adjust the solution pH to 8, and the ammonium conversion reaction time is 0.8h. At this time, the ammonium polyvanadate is completely dissolved to form an ammonium metavanadate solution. The impurity content in the solution is: Si 0.213g / L, Ca 0.1g / L, Al 0.087g / L, Na2O+K2O 0.76g / L.
[0086] 2) Add 5 mL / L of 10% polyaluminium chloride to the ammonium conversion solution for silicon removal. The silicon removal reaction is carried out at 75°C for 1 hour. The impurity contents of the silicon removal liquid obtained after filtration are: Si 0.076 g / L, Ca 0.069 g / L, Al 0.079 g / L, Na2O+K2O 0.506 g / L.
[0087] 3) The solution with silicon removal agent added was transferred to the electrophoretic sedimentation tank (the anode was a stainless steel electrode and the cathode was a graphite electrode) and electrophoretically sedimented for 0.8 h at a voltage of 0.3 V. After electrophoretic sedimentation, 1 g / L cationic polyacrylamide with a molecular weight of 30 million and 5 mL / L was added to the electrophoretic sedimentation tank for flocculation sedimentation. After standing for 2 minutes, the solution was filtered to obtain a clarified impurity-removed liquid. The impurity components of the impurity-removed liquid were: Si 0.018 g / L, Ca 0.059 g / L, Al 0.049 g / L, and Na2O+K2O 0.206 g / L.
[0088] 4) adjusting the pH of the solution to 8.5, and then cooling and crystallizing, the crystallization temperature is 40°C, the crystallization time is 3 hours, and the slurry is filtered after crystallization to obtain high-purity ammonium metavanadate and crystallization mother liquor, and the crystallization mother liquor is returned to step (1) for ammonium conversion reaction. The impurity components of the crystallization mother liquor are: Si 0.018g / L, Ca 0.039g / L, Al 0.044g / L, Na2O+K2O 0.218g / L.
[0089] The high-purity ammonium metavanadate finally produced has a purity of 99.79%, and the impurity contents are 0.016% Si, 0.034% Ca, 0.023% Al, and 0.2% Na2O+K2O.
[0090] Example 7
[0091] Ammonium polyvanadate with a V2O5 content of 87.2% was selected as a purification raw material, wherein the impurity content was: Si 0.32%, Ca 0.13%, Al 0.13%, and the sum of Na2O and K2O 1.3%.
[0092] 1) Ammonium polyvanadate and hot water are mixed at a ratio of 15:1, heated and ammonia water is added to adjust the solution pH to 8, and the ammonium conversion reaction time is 1 hour. At this time, all the ammonium polyvanadate is dissolved to form an ammonium metavanadate solution. The impurity content in the solution is: Si 0.213g / L, Ca 0.087g / L, Al 0.087g / L, Na2O+K2O0.867g / L.
[0093] 2) Add 2 mL / L of 12% polyaluminium sulfate to the ammonium conversion solution for silicon removal. The silicon removal reaction is carried out at 82°C for 1 hour. The impurity contents of the silicon removal liquid obtained after filtration are: Si 0.043 g / L, Ca 0.059 g / L, Al 0.07 g / L, Na2O+K2O 0.706 g / L.
[0094] 3) The solution with silicon removal agent added was transferred to an electrophoretic sedimentation tank (anode was a nickel electrode, cathode was a graphite electrode), and electrophoretic sedimentation was performed at a voltage of 0.8 V for 1 hour. After electrophoretic sedimentation, 1 g / L cationic polyacrylamide with a molecular weight of 25 million and 5 mL / L was added to the electrophoretic sedimentation tank for flocculation sedimentation, and filtered after standing for 2 minutes. After filtration, a clarified impurity-removed liquid was obtained, and the impurity components of the impurity-removed liquid were: Si 0.023 g / L, Ca 0.059 g / L, Al 0.059 g / L, and Na2O+K2O 0.36 g / L.
[0095] 4) adjusting the pH of the solution to 8.5, and then cooling and crystallizing, the crystallization temperature is 30°C, the crystallization time is 2.8 hours, and the slurry is filtered after crystallization to obtain high-purity ammonium metavanadate and crystallization mother liquor, and the crystallization mother liquor is returned to step (1) for ammonium conversion reaction. The impurity components of the crystallization mother liquor are: Si 0.023g / L, Ca 0.049g / L, Al 0.055g / L, Na2O+K2O 0.186g / L.
[0096] The high-purity ammonium metavanadate finally produced has a purity of 99.53%, and the impurity contents are respectively 0.015% Si, 0.044% Ca, 0.033% Al, and 0.22% Na2O+K2O.
[0097] Comparative Example 1
[0098] For comparison of purification effects, polyaluminium chloride was not added for silicon removal, and the other conditions were the same as those in Example 3.
[0099] The high-purity ammonium metavanadate finally produced has a purity of 98.6%, and the impurity contents are respectively 0.392% Si, 0.163% Ca, 0.114% Al, and 0.61% Na2O+K2O.
[0100] Comparative Example 2
[0101] For comparison of purification effects, no flocculant was added for sedimentation, and the other conditions were the same as those in Example 3.
[0102] The high-purity ammonium metavanadate finally produced has a vanadium purity of 98.8%, and the impurity contents are 0.121% Si, 0.044% Ca, 0.062% Al, and 0.87% Na2O+K2O.
[0103] Comparative Example 3
[0104] For comparison of purification effects, after adding the flocculant, the filtrate was directly filtered without standing and settling, and the other conditions were the same as those in Example 3.
[0105] The high-purity ammonium metavanadate finally produced has a vanadium purity of 99.4%, and the impurity contents are 0.022% Si, 0.041% Ca, 0.052% Al, and 0.31% Na2O+K2O.
[0106] Comparative Example 4
[0107] For comparison of purification effects, aqueous ammonia was added to adjust the pH of the ammonium transfer solution to 7.5, and the other conditions were the same as in Example 3.
[0108] The high-purity ammonium metavanadate finally produced has a vanadium purity of 98.4%, and the impurity contents are 0.322% Si, 0.043% Ca, 0.051% Al, and 0.59% Na2O+K2O.
[0109] Comparative Example 5
[0110] For comparison of purification effects, aqueous ammonia was added to adjust the pH of the ammonium transfer solution to 9.5, and the other conditions were the same as in Example 3.
[0111] The high-purity ammonium metavanadate finally produced has a vanadium purity of 98.3%, and the impurity contents are 0.383% Si, 0.042% Ca, 0.053% Al, and 0.57% Na2O+K2O.
[0112] Comparative Example 6
[0113] For comparison of purification effects, the amount of silicon removal agent added was 0.5 mL / L, and the other conditions were the same as in Example 3.
[0114] The high-purity ammonium metavanadate finally produced has a vanadium purity of 99.3%, and the impurity contents are 0.042% Si, 0.038% Ca, 0.055% Al, and 0.40% Na2O+K2O.
[0115] Comparative Example 7
[0116] For comparison of purification effects, the amount of silicon removal agent added was 7 mL / L, and the other conditions were the same as in Example 3.
[0117] The high-purity ammonium metavanadate finally produced has a vanadium purity of 99.43%, and the impurity contents are 0.041% Si, 0.037% Ca, 0.049% Al, and 0.38% Na2O+K2O.
[0118] The purity of the ammonium metavanadate prepared by purification in the above Examples 1-7 and Comparative Examples 1-7 and the content of related impurities are summarized in Table 1.
[0119] Table 1:
[0120]
[0121]
[0122] in conclusion:
[0123] In the above Examples 1-7, a multi-step method combining flocculation impurity removal-electrophoresis enhanced impurity removal-ammonium metavanadate crystallization is used, and each step is effectively coordinated to effectively reduce the silicon content in ammonium metavanadate to below 200 ppm, thereby achieving the purpose of efficient desiliconization. Through comparative examples, it is found that adding different silicon removal agents and flocculants is particularly important for the preparation of high-purity ammonium metavanadate, and a certain period of static sedimentation is also required, otherwise the silicon removal effect will be poor.
[0124] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing high-purity ammonium metavanadate by efficient silicon removal, characterized in that the steps include: S1. After the ammonium polyvanadate is dissolved, aqueous ammonia is added to perform a transammonium reaction to obtain an ammonium solution; S2 control the pH value of the ammonium solution to 8-8.5, adding a silicon removal agent for silicon removal reaction; the silicon removal agent is polyaluminum chloride and / or polyaluminum sulfate; S3. The solution after the silicon removal reaction is placed in an electric sedimentation tank for electrophoretic sedimentation, and a flocculant is added and allowed to settle, and the purified liquid is filtered; the flocculant is a cationic polyacrylamide; S4. Cooling and crystallizing the purified liquid, and filtering to obtain high-purity ammonium metavanadate.
2. The method according to claim 1, characterized in that In step S1, the impurities in the ammonium polyvanadate include: Si 0.3-0.8%, Ca 0.1-0.3%, Al 0.1-0.3%, and the sum of Na2O and K2O 1.2-2.4%; And / or, the content of V2O5 in the ammonium polyvanadate is 85-90%.
3. The method according to claim 1, characterized in that In step S1, during the transammonium reaction, ammonia water is added to a pH of 7-9, and the transammonium reaction time is 0.5-1 h.
4. The method according to claim 1, wherein In step S2, the concentration of the desiliconizing agent is 10-15 wt %, and the amount of the desiliconizing agent used per liter of ammonium conversion solution is 2-5 mL.
5. The method according to claim 1 or 4, characterized in that In step S2, the reaction temperature of the desiliconization process is 75-85° C., and the desiliconization reaction leaching time is 1-2 hours.
6. The method according to claim 1, characterized in that In step S3, the voltage of the electrophoretic sedimentation process is 0.3-0.8V, and the sedimentation time is 0.5-1h; And / or, the anode of the electrophoretic sedimentation tank is a stainless steel electrode, a nickel electrode, or a ruthenium-plated titanium electrode, and the cathode is a graphite electrode or a glassy carbon electrode.
7. The method according to claim 1, characterized in that In step S3, the molecular weight of the flocculant is 10 million to 30 million; And / or, the concentration of the flocculant is 1-3 g / L, the amount of flocculant added to each liter of silicon removal reaction solution is 5-10 mL, and the static sedimentation time is 2-5 min.
8. The method according to claim 1, characterized in that In step S4, the pH value of the crystallization process is 8.5-9; And / or, the crystallization temperature is 30-50° C., and the crystallization time is 2-4 hours.
9. The method according to claim 1, characterized in that In step S4, the mother liquor obtained after the crystallization filtration is used to dissolve ammonium polyvanadate in step S1.
10. The method according to claim 1 or 9, characterized in that In step S1, the liquid-to-material ratio used for dissolving the ammonium polyvanadate is (15-20):1.
Citation Information
Patent Citations
Method for purifying vanadium pentoxide
CN104843789A
Method for preparing high-purity vanadium pentoxide by synergistically removing silicon and chromium in vanadium solution through nickel ions
CN114480883A
Sodium-free vanadium-phosphorous oxide catalyst and preparation method thereof
CN109569679A
Preparation method of high-purity vanadium pentoxide suitable for vanadium electrolyte
CN115196676A
Method for preparing high-purity vanadium pentoxide from ammonium polyvanadate
CN116177601A
Cited By
Method for removing silicon from sodium vanadium solution
CN121377112A